Kale improves bowel movements in constipated women and affects some intestinal microbes and metabolites: a pilot study - Nishimoto, Yuichiro; Salim, Felix; Yamauchi, Yohsuke; Mori, Yuka; Murakami, Shinnosuke; Suzuki, Asahi; Fukuda, Shinji; Yamada, Takuji (Frontiers in Nutrition, 2023)
Dietary fiber improves intestinal environments, by, among others, increasing stool frequency. Kale is a good source of dietary fiber and minerals; however, the effects of kale on the intestinal environment have not yet been evaluated. This study determined how the intestinal environment, including the intestinal microbiota and its metabolome, and stool frequency are affected by the consumption of kale, in humans. A randomized controlled crossover trial, with a 4-week consumption of kale or control food, was conducted. An integrated analysis of the intestinal microbiota and metabolome was performed, and their relationship with improvements in stool frequency was analyzed. Kale intake for 4 weeks significantly increased stool frequency and altered some intestinal microbes, such as an increase in the [Eubacterium] eligens group and a decrease in the [Ruminococcus] gnavus group. Analysis of subjects with increased stool frequency revealed that this group had smaller amounts of stool before kale intake. Our findings indicate that kale modifies certain gut microbes, such as [Eubacterium] eligens and [Ruminococcus] gnavus, and improves bowel movements, particularly in those with smaller stool amounts.